New onset diabetes after transplantation (NODAT) in renal transplant recipients: a study from tertiary care center in Kashmir, India - Ahmed, Mehroz; Sudan, Rahul; Wani, Imtiyaz Ahmed; Wani, Muzaffar Maqsood; Banday, Khurshid Ahmed; Gupta, Gunjan (International Journal of Research in Medical Sciences, 2018)
Background: New onset diabetes after transplantation (NODAT) is a common entity in the post-transplant period after several types of organ transplants like kidney, liver heart and lungs. NODAT is a common complication after solid organ transplantation and has been reported to have an adverse impact on patient and allograft outcomes. Risk stratification and intervention to minimize risk should be an integral part of management of transplant recipients. Methods: A total of 100 patients who underwent renal transplantation were observed for the development of NODAT in the post transplantation period. Patients were evaluated in the pre- transplant and post-transplant period. Risk factors which were associated with the development of NODAT were analyzed. Results: Out of 100 patients, 79 were males and 21 were females. The mean age of the patients undergoing renal transplantation was 40 years. The youngest patient was 18 years old and the eldest was 64 years old. Majority of the patients were in the age group of 31 to 50 years (60 patients, 60%). The incidence of NODAT in present study was 17%. The major risk factors for the development of NODAT were identified as male sex, positive family history of diabetes, history of alcohol intake before renal transplantation, hypertriglyceridemia, post renal transplantation hypomagnesemia, proteinuria, and use of drugs like tacrolimus and prednisolone. Conclusions: NODAT has been identified as a risk factor for graft rejection, long-term graft failure, and decreased patient survival. Once NODAT has been diagnosed, specific anti-hyperglycemic therapy is essential to reach a tight glycemic control, which contributes to significantly reduced post-transplantation morbidity. Due to the importance of NODAT, diabetes education and its impact on the outcome of post-transplantation morbidity and mortality becomes crucial point of research among organ transplantation populations. Diabetes education in a group setting can be adopted for organ transplantation recipients with NODAT.